Defining Disaster-Related Health Risk: A Primer for Prevention. Issue 3 (1st June 2018) - Keim, Mark
Abstract: Effective disaster risk management requires not only management of the immediate problem (disaster-related injuries and disease), but also of the patient's risk factors and of the underlying health determinants. This requires an accurate and well-validated process for assessment of the determinants of disease. Ideally, disaster risk management is based on a prioritization process. Once hazards have been identified, they are assessed in terms of the probability and impact in terms of losses. The hazards associated with the greatest probability and impact loss are prioritized. In addition to prioritization, risk assessment also offers a process for ongoing research involving the interaction of health determinants, risk, and protective factors that may contribute to future adverse health outcomes. Recently, assessments of health risk have become an integral part of local, state, and national emergency preparedness programs. One of the strengths of these assessments is the convening of multi-sectoral input for public health decision making and plans. However, this diversity of input also creates challenges in development of a common nomenclature for assessing and communicating the characteristics of this risk. Definitions remain ambiguous for many of the key indicators of disaster risk, especially those applied to health risk. This report is intended as a primer for defining disaster-related health risk. This framework is discussed within a nomenclature that is consistent with international standards for risk management and public health prevention. M Keim .Defining disaster-related health risk: a primer for prevention .Prehosp Disaster Med .2018 ;33 (3 ):308 -316 .